Financing energy projects: Modeling valuation and risk assessment in Turkish energy market - Berk, Cem (My University, 2010)
ENERJĐ PROJELERĐNĐN FĐNANSMANI: TÜRKĐYE ENERJĐ PĐYASASINDA DEĞERLEME VE RĐSK TESPĐTĐ MODELLEMESĐ Dünya'daki fosil enerji kaynaklarının tükenmekte olduğuddan enerji projelerinin finansmanı çağdas finansman anlayısıyla özellikle gelismekte olan ülkeler için yeni ve önemli bir konudur ve genis bir sekilde ele alınabilir. Gelismekte olan ülkelerin artan enerji talebi enerji piyasalarını yeniden sekillendirmistir. Küresel enerji piyasaları entegre hale gelmekte, serbestlesme , seffaflık, enerji arz güvenliği, ve iklim değisikliği politikaları gelismis enerji piyasalarında uygulanmaktadır. Petrol, kömür, doğalgaz ve yenilenebilir enerji gibi farklı enerji kaynakları benzer avantaj ve fırsatlara sahip olsa da farklı finansal dinamikleri bulunmaktadır. Enerji projelerinin , özellikle yenilenebilir enerji, tarife, tesvik , ve piyasa bazlı müdahaleleriyle finansal yapılabilirlik kazanmaktadır. Yazar tarafından hazırlanan bir Ege Proje değerlemesi de dahil olmak üzere enerji projelerinin değerlemesi çalısılmıstır. Enerji projelerinin finansmanının farklı yolları analiz edilmistir. Çalısmada finansman temininde kritik olan projelerin riskleri ve konrolüne iliskin araçlar vurgulanmaktadır. Nihayet Türkiye elektrik piyasasının değerlendirmesi yapılarak, tekel pozisyonundaki kamu otoritesinin talep tahmin yöntemi analiz edilmistir. Yöntemin verimliliği rise maruz değer yaklasımı yoluyla test edilmektedir.

FINANCING ENERGY PROJECTS: MODELING VALUATION AND RISK ASSESSMENT IN TURKISH ENERGY MARKET Financing energy projects with the understanding of modern finance is a new and important topic especially for the emerging economies as fossil energy sources are rapidly demolishing in the World and it is a widely discussable topic. Increasing demand for energy of emerging countries has restructured the energy markets. The global energy markets are becoming integrated; where liberalization, transparency, security of energy supply and climate change policies are applied in the developed energy markets. Although they are subject to similar opportunities and obstacles in the industry, different sources of energy such as oil, gas, coal or other renewable energy sources have different financial dynamics. Energy projects, particularly renewable energies, require governmental interference in terms of tariffs, incentives and market based solutions for being financially feasible. Valuation of energy projects are studied with the inclusion of an Aegean energy project appraisal which is prepared by the author. Different ways of obtaining financing for the projects are analyzed. In the study, the risks and mitigation instruments for the projects are underlined which are crucial for the financing of the projects. Finally a critical review of Turkish electricity market is given where the demand forecast methodology of monopoly government authority is analyzed. The efficiency of the methodology is tested through value at risk approach.
Keywords: Enerji Pazarlaması_Türkiye; Finans; Muhasebe; Pazarlama; Risk Yönetimi